(untitled) (Coffee Science - ISSN 1984-3909, 2012)
The experiment was conducted in Caiana district on two contiguous farms in the town of Machado, South of Minas Gerais with the objective of evaluating the contents of micronutrients in the soil and coffee plant leaves in systems of agroforestry and conventional management as compared with the native forests in the South of Minas Gerais. Soil samples for the chemical analyses of micronutrients at the depths of 0 20 and 20 40 cm were taken with determination of pH, organic matter, Zn, Fe, Mn, Cu and B. The soil samples were performed in three stripes of land with different managements, amounting to 24 samples: [(2 depths x 2 managements with coffee plants x 4 replicates) + (2 depths x 1 management with native forest x 4 replicates)]. Foliar tissue samples were conducted on the coffee plants for nutritional evaluation of the contents of boron, Zn, Cu, Fe and Mn. The experimental design was of randomized blocks with three treatments and four replicates. The statistical analysis was undertaken through the statistical program SISVAR and the comparison of the means was done by Scott-Knott test with 5% of probability. The coffee plant cultivated under the agroforestry system proved effective in micronutrient cycling owing to the adequate contents presented in foliar tissue for producing coffee plants with the exception of zinc which was low. This result can be accounted for by the continuous supply of plant matter to the soil that over time, after the decomposition process, micronutrients are released to the soil and afterwards for absorption by the plants.